Grey is the new black: covert action and implausible deniability - Cormac, Rory; Aldrich, Richard J. (Oxford University Press, 2018)
For generations scholars have defined covert action as plausibly deniable interventions in the affairs of others; the sponsor’s hand is neither apparent nor acknowledged. We challenge this orthodoxy. Turning the spotlight away from covert action and onto plausible deniability itself, we argue that even in its supposed heyday, the concept was deeply problematic. Changes in technology and the media, combined with the rise of special forces and private military companies, gives it even less credibility today. We live in an era of implausible deniability and ambiguous warfare. Paradoxically, this does not spell the end of covert action. Instead, leaders are embracing implausible deniability and the ambiguity it creates. We advance a new conception of covert action, historically grounded but fit for the twenty-first century: unacknowledged interference in the affairs of others.